2017
DOI: 10.1021/acs.nanolett.7b03797
|View full text |Cite
|
Sign up to set email alerts
|

Bright Electroluminescence from Single Graphene Nanoribbon Junctions

Abstract: Thanks to their highly tunable band gaps, graphene nanoribbons (GNRs) with atomically precise edges are emerging as mechanically and chemically robust candidates for nanoscale light emitting devices of modulable emission color. While their optical properties have been addressed theoretically in depth, only few experimental studies exist, limited to ensemble measurements and without any attempt to integrate them in an electronic-like circuit. Here we report on the electroluminescence of individual GNRs suspende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 56 publications
5
87
0
Order By: Relevance
“…At higher voltage (V > 1.9 V), no further spectral features were observed. ( c ) and ( e ) confirm the shift in emission line as a function of Z and V, respectively [ 140 ].…”
Section: Figures Scheme and Tablesmentioning
confidence: 63%
See 2 more Smart Citations
“…At higher voltage (V > 1.9 V), no further spectral features were observed. ( c ) and ( e ) confirm the shift in emission line as a function of Z and V, respectively [ 140 ].…”
Section: Figures Scheme and Tablesmentioning
confidence: 63%
“…Particularly, the EL effect has also been reported from graphene-based materials. The EL footprints have been demonstrated from single to a few layers of graphene structure [ 57 ] such as carbon nanotubes [ 139 ], carbon nanoribbons [ 140 ], and quantum dots [ 141 ].…”
Section: Electroluminescence (El) Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 First experiments with GNRs incorporated into devices have shown that the ribbon length as well as their overall integrity are essential for realizing the inherent potential of this material. 13,14 However, methods suited to estimate the length of the GNRs after transfer onto device substrates are lacking.…”
mentioning
confidence: 99%
“…Introducing defects in two-dimensional materials is therefore of interest for future applications in nanotechnology where individual carbon-based molecular components are linked electrically and ensure at the same time enhanced flexibility in the architecture of the final circuits. In addition, these defects might also be used to locally tune the electronic or optical properties of the molecular wire [46], similar to semiconductor devices.…”
mentioning
confidence: 99%